2014
DOI: 10.1111/acer.12466
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between a History of Binge Drinking During Adolescence and Self-Reported Responses to Alcohol in Young Adult Native and Mexican Americans

Abstract: BACKGROUND Binge drinking during adolescence is common and may predict increased drinking in young adulthood and enhanced risk for alcohol dependence. Variation in level of response to the hedonic and adverse effects of alcohol is in part an inherited factor that may also influence its use, abuse and dependence. The present study investigated, in young adults, whether an association could be demonstrated between variation in self-reported responses to alcohol and a history of binge drinking during adolescence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…The lifetime prevalence of substance dependence in this sample and associations with acculturation stress and other comorbid mental disorders has been previously reported (Criado and Ehlers, 2007; Criado et al, 2013; Ehlers and Phillips, 2007; Ehlers et al, 2009, 2010, 2011, 2012, 2014; Gilder et al, 2007; Norden-Krichmar et al, 2014). Specifically, lifetime diagnoses of alcohol dependence, substance dependence, and anxiety disorders were associated with elevations in acculturation stress.…”
Section: Introductionsupporting
confidence: 59%
“…The lifetime prevalence of substance dependence in this sample and associations with acculturation stress and other comorbid mental disorders has been previously reported (Criado and Ehlers, 2007; Criado et al, 2013; Ehlers and Phillips, 2007; Ehlers et al, 2009, 2010, 2011, 2012, 2014; Gilder et al, 2007; Norden-Krichmar et al, 2014). Specifically, lifetime diagnoses of alcohol dependence, substance dependence, and anxiety disorders were associated with elevations in acculturation stress.…”
Section: Introductionsupporting
confidence: 59%
“…The present study is similar to previous research which reported that a history of self-reported health status could facilitate increased reporting of alcohol use [14]. Another study conducted by Wellman, Contreras, Dugas, and O'Loughlin [36] found a correlation between negative self-reported health status and increased alcohol use in young adults.…”
Section: Discussionsupporting
confidence: 91%
“…Others have shown that consuming alcohol at an early age is correlated with risk propensity for suicide, violence, delinquency, and other unproductive behaviors [11,12]. Also, individuals who start drinking prior to age 21 tend to be more likely to engage in alcohol use than those who delay consuming alcohol until at least age 21 [13,14]. In addition, early alcohol initiation predicts vulnerability for current, recurrent and lifetime alcohol use disorders [15].…”
Section: Introductionmentioning
confidence: 99%
“…7,13,2227 The purpose of the present set of analyses was to investigate: (1) the prevalence of, and levels of drinking (quantity and frequency) in, the 3 DSM-5 AUDs (mild moderate, severe) in the two populations evaluated and (2) the clinical course of AUD as defined by the age of onset, occurrence, sequence, and progression of 36 alcohol-related life events, in non-treatment seeking young adult Mexican and Native American males and females. Additionally, we evaluated whether the sequence of occurrence of these AUD associated life events differed depending on whether the individual had a diagnosis of mild, moderate, or severe AUD.…”
Section: Introductionmentioning
confidence: 99%